KEBIJAKAN DAN PERMASALAHAN AKSES PENDIDIKAN DASAR - Amanda Nala Fatricia; Syahdilla Febriani; Rizki Ananda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The 1945 Constitution guarantees the basic right of all citizens to obtain basic education. The Indonesian government has made a number of initiatives, including the Smart Indonesia Program (PIP), the zoning system, and the elimination of the National Examination, to ensure equal access to education. However, in reality, these steps have not been fully successful in overcoming barriers to access to education, especially in underprivileged, isolated, and marginalized communities. This study aims to critically examine Indonesia's basic education regulations and identify issues that hinder equal access to education. The approach taken is a literature review, which involves reviewing various scientific publications, government policies, and previous study findings. The study findings indicate that geographical, economic, and infrastructure constraints, as well as a lack of trained teachers, continue to influence the gap in access to education. Furthermore, the gap in access is exacerbated by inconsistent implementation and lack of policy socialization. Obtaining government funding is also very difficult for small private and religious educational institutions. Therefore, to ensure equal access to basic education, a more inclusive and contextual strategy and a comprehensive policy evaluation are needed. Building superior and competitive human resources in the era of globalization requires equal and high-quality education.